The role of conserved residues in the catalytic activity of NDM-1: an approach involving site directed mutagenesis and molecular dynamics. Issue 32 (2nd August 2019) - Ali, Abid; Kumar, Rakesh; Iquebal, Mir Asif; Jaiswal, Sarika; Kumar, Dinesh; Khan, Asad U.
Abstract : Drug degraded by enzyme and hence not targeted on to the cell leading to cell survival. After mutation leading to conformational changes and loss of function hence drug was not degraded and remained available for the target to lyse the cell. Abstract : The rise of New Delhi metallo-beta-lactamase-1 (NDM-1) producers is a major public health concern due to carbapenem resistance. Infections caused by carbapenem-resistant enterobacteria (CRE) are classified as a serious problem. To understand the structure and function of NDM-1, an amino acid replacement approach is considered as one of the methods to get structural insight. Therefore, we have generated novel mutations (N193A, S217A, G219A and T262A) near active sites and an omega-like loop to study the role of conserved residues of NDM-1. The minimum inhibitory concentrations (MICs) of ampicillin, imipenem, meropenem, cefotaxime, cefoxitin and ceftazidime for all mutants were found to be reduced 2 to 6 fold, compared to a wild type NDM-1 producing strain. The K m values increased while K cat and K cat / K m values were decreased compared to wild type. The affinity as well as the catalysis properties of these mutants were reduced considerably for imipenem, meropenem, cefotaxime, cefoxitin, and ceftazidimem compared to wild type, hence the catalytic efficiencies ( K cat / K m ) of all mutant enzymes were reduced owing to the poor affinity of the enzyme. The IC50 values of these mutants with respect to each drug were reduced compared to wild type NDM-1. MD simulations and docking results from the mutant protein models, along with the wild type example, showed stable and consistent RMSD, RMSF and R g behavior. The α-helix content values of all mutant proteins were reduced by 13%, 6%, 14% and 9% compared to NDM-1. Hence, this study revealed the impact role of active sites near residues on the enzyme catalytic activity of NDM-1.